Factors Associated with Nurses\' Participation in Clinical Decision Making - L Rostamniya; V Ghanbari; E Kazemnejad Leili; A Pasha; A Karimi Rozveh; E Pariyad (Iran University of Medical Sciences, 2014)
Abstract   Background & Aims: Collaboration of health care team in clinical dicision making is a key factor to provide safe and efficient care. Since nurses have the most continous contact with patients, they could have great influences on diagnostic and therapeutic decisions. The aim of this study was to determine nurses' collaboration in clinical decision-makings and its related factors.   Material & Methods: This descriptive, cross-sectional study was conducted among nursing staff of educational hospitals of Rasht-Iran. A total of 193 nurses were selected by stratified random sampling. Data was collected by Decision-making Activities Questionnaire (PDAQ) and analyzed by descriptive and inferential statistics including pearson corrolation test, Independent T test, One-way ANOVA and Generalized Estimating Equations (GEE) using SPSS-PC (v. 16).   Results: The mean score of nurses' collaboration in clinical decision-makings in all three dimentions (clarifying the problem, suggesting and evalutiong possible methos and selecting from one of suggested ways) was more than 50. Moreover, the findings revealed that the participation score of those with master degree, intersted in continuing their job at current ward, worked in intensive care units or in morning shifts have been significantly higher than other nurses (P<0.05). There was also a significant relationship between nurses' decision-making scores, their age and work experinces (P<0.05). Level of education, and present job experiance had the most positive effect, and high job experince and having no responsibility in working place had the most negative effect on nurses' level of clinical participation (P=0.00). Conclusion: Regarding the importance of nurses' collaboration in decision making and the influence of higher leveles of education and working in ICU, providing appropriate context for more participation of nurses in decision making processes is suggested.